Sustainable Development Goals and Islamic Social Finance: From Policy Divide to Policy Coherence and Convergence - Evren Tok (14779270) (2022)
This study aims to show how Islamic social finance (ISF) instruments can contribute to achieving SDGs and to filling the gaps in pressing humanitarian crises, such as refugee protection. ISF institutions enjoy sufficient financial capacity to bridge the gaps and realize the most relevant and urgent SDGs. However, due to policies and other constraints, their participation in international development aid programs is limited. Accordingly, this study explores the existing policy divide between Western and Islamic countries regarding the use of Faith-Based funds in international humanitarian and development aid programs. Through case studies, this study demonstrates that ISF instruments have the potential at national and international levels to mobilize resources to support marginalized groups in society in various countries. The analysis indicates the need to develop a framework that helps to build cooperation among local and international actors to mobilize ISF funds for cross-country development and humanitarian aid, which accelerates the achievement of the SDGs. This paper studies ongoing dialogues among various stakeholders to create policy convergence and to use ISF instruments towards SDGs. This study suggests that the dialogue should be more inclusive by including all potential stakeholders, including Muslim leaders, policymakers and Shariah Scholars, to narrow policy gaps and to draw policy coherence for using ISF tools in the duality aid programs and for creating synergies towards achieving the SDGs. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su14116875